Optimisation Of Ternary Green Diesel Blends For Diesel/Palm Methyl Ester/Alcohol Using Product Design Optimization - Razak, Nurul Hanim; Hashim, Haslenda; Yunus, Nor Alafiza; Klemeš, Jiří Jaromír; Phoon, Li Yee (Italian Association of Chemical Engineering (AIDIC), 2019)
Among many alternative fuels, oxygenated fuels like biodiesel and biomass-based energy (biofuel) such as bioalcohol have greater potential to enhance engine performance and mitigate particulate exhaust emissions in compression-ignition (CI) engines. The main objective of this study is to determine the optimal ternary green diesel (GD) blends formulation by identifying the most feasible diesel/biodiesel/alcohol that meeting the ASTM D975, Standard Specification for petro-diesel. Three steps of product design optimization (PDO) has been performed, (1) specify the fuel target properties based on Euro5; (2) optimize the formulation for ternary GD blends; (3) rank and select the optimal ternary GD blends. The ranking and selecting the optimal ternary GD blends were focused on the correlation of the higher cetane number (CN) over the cost of fuel. The PDO model indicated the most cost-effective and environmentally friendly diesel/biodiesel/alcohol ternary GD blends shall contain 74 % Malaysia petro-diesel, 16 % palm methyl ester (PME) and 1 % of butanol. Notably, the higher CN, the shorter the fuel ignition and the better the combustion efficiency. High CN fuels can significantly burn faster and more completely and hence reduce the harmful exhaust emissions such as SO2.